Stroma cells stimulate colorectal tumor cells to increase expression of tumor-promoting RAC1b - Pereira, Joana (2018)
An inflammatory microenvironment is a tumor-promoting condition that provides survival signals to which cancer cells respond with changes in their gene expression. One key gene regulatory mechanism that responds to extracellular signals is alternative splicing. For example RAC1B, a RAC1 alternative splicing variant that we previously identified in a subset of BRAF-mutated colorectal tumours, was found increased in samples from inflammatory bowel disease patients or following experimentally-induced acute colitis in a mouse model. The main goal of this work is to determine the pro-inflammatory signals that lead to increased RAC1b expression in colorectal cells.